The Effect of Combined Suction Techniques on Peep and Oxygen Saturation in ICU Patients: A Systematic Review - Arif Mubarok; Iwan Purnawan; Imaningtyas Ridar (Indonesian Journal of Global Health Research, 2026)
Suction techniques in mechanically ventilated ICU patients affect important respiratory parameters, such as Positive End Expiratory Pressure (PEEP) and oxygen saturation. Open suction techniques can cause significant reductions in these parameters, necessitating a systematic evaluation of the effectiveness of combined suction techniques. The aim of this study is to provide evidence-based recommendations regarding the effects of combined suction techniques on PEEP and oxygen saturation in ICU patients. A systematic search was conducted in five databases of PubMed, ScienceDirect, EBSCO, and other databases was conducted for studies published between 2014 and 2024. The keyword using in English included “combined suction”, “Ventilator”, “ICU”, “PEEP” and oxygen saturation. From the initial search, a total of 41 articles were identified. Ten full-text papers underwent a thorough evaluation after titles and abstracts were filtered according to the inclusion criteria (language, publication year, and open-access availability). Ten papers were chosen for final analysis after being critically evaluated and their applicability to the study's goals was evaluated. PRISMA guidelines were followed for study selection, and data extraction focused on PEEP and oxygen saturation results. A total of Based on 10 included literatures, it was shown that combined suction technique resulted in less decrease in PEEP and oxygen saturation compared to open suction technique. Pooled analysis showed that combined suction was superior in maintaining alveolar pressure and oxygenation during suctioning. The combined suction technique is more effective than the open suction technique in maintaining PEEP and oxygen saturation in mechanically ventilated ICU patients.